The relationship between students' learning styles and academic performance in accounting / Wan Mardyatul Miza Wan Tahir - Wan Tahir, Wan Mardyatul Miza (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
A learning style is the distinctive method of an individual to process and comprehend new information and skills. Whereas learning a course like in the case of learning an accounting course for non-accounting students is always considered challenging as it requires students to understand the theory and application of accounting principles. As such, this paper investigates the relationship between students' learning style; adopted by non-accounting students in learning an accounting course; and the impact it has on their academic performance. The results show that there is a relationship between students' learning style and their academic performance statistically. Students who adopted pragmatist and theorist learning styles indicated a higher level of success in academic performance as compared to reflector and activist learning styles. This paper is expected to contribute to the literature of students' performance in an accounting course and learning styles adopted by the students majoring in other programmes using the Honey and Mumford learning style model.